Aspects and potentials of cogeneration using industrial waste as fuel - Sadewo, Yus; Mohanty, B.; Mora, Jean-Claude; Surapong Chiraratananon; Government of The Netherlands (Bangkok : Asian Institute of Technology, 1991)
The industrial waste for energy generation is available at low cost, but the utilization requires a high investment cost. This thesis studies the aspects and potentials of cogeneration using industrial waste as fuel in Indonesia. A model is system on a system. application developed based on an existing cogeneration paper mill to assess the performance of the A feasibility study for the cogeneration is also carried out in a plywood factory. The result from the paper cogeneration system should be power ratio of the plant. mill study shows that a designed to match the heat to Application of cogeneration system is crucial toward the electricity price. The cogeneration system is not feasible for electricity price at Rp 70 per kWh. At a price of Rp 84 per kWh, the payback period for cogeneration system at the plywood factory would be 8 years.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1991
Keywords: Waste products as fuel; Factory and trade waste; Cogeneration of electric power and heat